ON THE NUMBER OF SERVED CUSTOMERS IN BMAP(t)|G|∞ MODEL - Khajkhnidi, A. R. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2009)
In the present paper the BMAP(t)|G|∞ model with non-stationary input stream of customers is considered. The distribution of customers’ number served during time t and its mean value are obtained. Estimates for characteristics of MAP(t)|G|∞ and M^x(t)|G|∞ models are obtained as well.